AFIKSASI BAHASA DAYAK KANAYATN DALAM KITAB PAPAKATATN BARAHU - Astonis, St. Sempuen; Simanjuntak, Hotma; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractAffixation of Dayak Kanayatn Languange in Papakatatn Barahu is a morphology research that studied affixation of Dayak Kanayatn Language in a translation of New Testament Bible into a local language. This research is created because the affixation process that appears in translation need to be studied, so that’s will produce a comprehensive translation into a local language as form of language process.The problem in this research is divided into three subproblems that include form, function, and meaning of affixes in Dayak Kanayatn language. The affixation of Dayak Kanayatn language is describe in qualitative research that used descriptive method. The technique that used in collecting data is document study technique. The data source in this research is Papakatatn Barahu, a translation of New Testament Bible into Dayak Kanayatn language. The result of the data analyzed in this research is found prefix, suffix, konfiks, and affix combination that has various form, function, and meaning. Dayak Kanayatn prefix in Papakatatn Barahu has eight kinds which is ba-, di-, ka-, ma-, pa-, pa-, sa-, and ta-. Dayak Kanayatn suffix in Papakatatn Barahu has four kinds which is -atn, -nya, -i', -atn. Dayak Kanayatn konfiks in Papakatatn Barahu has five kinds which is ba-atn, ka-atn, pa-atn, pa-atn, and sa-nya. Dayak Kanayatn combination affix in Papakatatn Barahu has eleven kinds which is ma-.-atn, ma-.-i’, ba-.-atn, ba-.-atn, di-.-atn, di-.-i', di-.-pa-, di-.-pa-atn, di-.-pa-i’, m-.-pa-atn, ta-.-atn. All of those affixes has a forms, function, and meaning. Keywords: affixation, Dayak Kanayatn language, Papakatatn Barahu Bible.